2003
DOI: 10.1103/physrevb.68.035414
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiodensity functional investigation ofB24clusters: Rings, tubes, planes, and cages

Abstract: We investigate the equilibrium geometries and the systematics of bonding in various isomers of a 24-atom boron cluster using Born-Oppenheimer molecular dynamics within the framework of density functional theory. The isomers studied are the rings, the convex and the quasiplanar structures, the tubes and, the closed structures. A staggered double-ring is found to be the most stable structure amongst the isomers studied. Our calculations reveal that a 24-atom boron cluster does form closed 3-d structures. All iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
86
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 26 publications
2
86
0
1
Order By: Relevance
“…We also have studied some clusters. Figure 1 shows the double-ring structures for B 24 and B 32 [14,15] along with clusters constructed by us. The new B 24 cluster with a hexgon hole is less favorable by 0.08 eV/atom while the B 32 is more favorable by 0.03 eV/atom than the corresponding doublering.…”
Section: Flat Triangular Buckled Triangularmentioning
confidence: 99%
See 2 more Smart Citations
“…We also have studied some clusters. Figure 1 shows the double-ring structures for B 24 and B 32 [14,15] along with clusters constructed by us. The new B 24 cluster with a hexgon hole is less favorable by 0.08 eV/atom while the B 32 is more favorable by 0.03 eV/atom than the corresponding doublering.…”
Section: Flat Triangular Buckled Triangularmentioning
confidence: 99%
“…The hexagonal graphitic BS was found to be unstable [11,18]. Based on extensive theoretical studies of boron clusters [11,12,13,14,15], an Aufbau principle was proposed whereby the most stable structures should be composed of buckled triangular motifs [12] . Experiments on small clusters of 10-15 atoms support this view [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Another possible kind of basic unit for synthesizing BNT is the double-ring tubular ͑DRT͒ clusters. Such idea is mainly based on the fact that the DRT configuration is the most stable structure among various isomers of B 20 , B 24 , B 30 , B 36 , and B 96 clusters. [20][21][22][23] Moreover, the DRT clusters have been detected in experiments.…”
mentioning
confidence: 99%
“…Such idea is mainly based on the fact that the DRT configuration is the most stable structure among various isomers of B 20 , B 24 , B 30 , B 36 , and B 96 clusters. [20][21][22][23] Moreover, the DRT clusters have been detected in experiments. 25 Our previous study also showed that for large sized boron clusters the three-ring tubular and DRT configuration are more stable than other ones.…”
mentioning
confidence: 99%